Analysis of the Experience of Teachers on Student Achievement in Economics at Private High School - Ratnawita Ratnawita; Saut Maruli Tua Pandiangan; Arief Budi Pratomo; Eka Kurnia Saputra; Uli Wildan Nuryanto (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research is to analyze the experience of economics education teachers on student achievement in economics at Private High Schools. This research uses a causal research type with a quantitative approach. Population in this study are Private High Schools Students in Medan City in 2022. Sample is taken randomly using snowball sampling technique. So, sample in this study are 100 Private High Schools Students in Medan City. The data analysis method used simple linear regression analysis. The results show that the experience of economics education teachers has significant effect on student achievement in economics at Private High Schools.